Roles of Social Networking in Complex Multi-agency Implementation Efforts. (September 2022) - Estrich, Cameron; DeSisto, Carla L.; Pliska, Ellen; Mackie, Christine N.; Velonis, Alisa; Uesugi, Keriann; Waddell, Lisa F.; Rankin, Kristin M.
Some state health departments in the United States are in the process of increasing access to immediate postpartum long-acting reversible contraception (LARC), an evidence based approach to preventing unintended pregnancy. Changing state Medicaid policies for immediate postpartum LARC reimbursement has proven insufficient for overcoming access barriers, so states developed implementation strategies to conduct multiple, coordinated systems changes. This research was conducted to understand the roles of social networks in implementing a complex health systems change. In 2015 and 2018, semi-structured telephone interviews were conducted with state teams engaged in increasing access to immediate postpartum LARC. Transcriptions of interviews were coded based on the Consolidated Framework for Implementation Research and implementation strategies, then themes were refined through discussion. A web-based assessment in 2018 evaluated degree of implementation accomplishment. Teams found that increased formal or informal social engagement among members aided timeliness, resource coordination, accountability, and enthusiasm, and over the course of 2 years, reduced disruptions due to staff turnover. The composition of the team influenced the social ties it could draw upon. Preexisting relationships were the most common source of social networking. Bridging social ties connected state teams to novel information and instrumental aid used to seek funding, conduct consumer awareness activities, and train healthcare providers. Cultivating and maintaining relationships among agencies and organizations as part of routine operations enables them to be available for future implementation efforts. Multi-agency teams may benefit from prioritizing time for internal and external relationship-building to enhance implementation progress.